DIAGNOSIS KESULITAN BELAJAR DALAM PERSPEKTIF AL-QUR’AN - Sari, Windy Dian (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2025)
This paper examines verses of the Qur'an on the diagnosis of student learning difficulties. Learning difficulties or problems can be known based on symptoms manifested in various forms of behavior, both cognitively, affectively, and psychomotorly. This paper uses a descriptive qualitative approach. The results showed that the diagnosis of the Qur'ani can be done through three stages, namely understanding students who have disorders, localizing learning difficulties, and detecting learning difficulties in depth while providing appropriate alternative solutions. The solution given to students who have learning difficulties is to perform stages according to student needs